2008
DOI: 10.1002/pmic.200700824
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous proteomic analysis of proliferative vitreoretinopathy

Abstract: Proliferative vitreoretinopathy (PVR) is the most common cause of anatomic failure in retinal detachment surgery. To understand the molecular mechanisms, vitreous proteomes of patients with PVR were investigated by two-dimensional-nano-liquid chromatography coupled with tandem mass spectrometry. Vitreous samples of moderate PVR (grade B), and severe PVR (grade C or D) were aspirated during pars plana vitrectomy before infusion. In the current study, 129, 97 and 137 proteins were identified in vitreous of norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 36 publications
4
81
0
Order By: Relevance
“…Although the formation of AGEs is a natural process that occurs with aging and nearly all proteins in the body carry some burden of glycation (Monnier et al, 1992), the rate of AGE formation is accelerated in diabetic conditions due to persistent hyperglycemia and oxidative stress (Baynes and Thorpe, 1999). Several studies in the eye have shown an association between the level of AGE products in the vitreous and the clinical progression of DME (Stitt et al, 1998; Yokoi et al, 2005; Yu et al, 2008). To control appropriate responses, cells have a pattern recognition receptor (RAGE) to detect the levels of AGEs in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Although the formation of AGEs is a natural process that occurs with aging and nearly all proteins in the body carry some burden of glycation (Monnier et al, 1992), the rate of AGE formation is accelerated in diabetic conditions due to persistent hyperglycemia and oxidative stress (Baynes and Thorpe, 1999). Several studies in the eye have shown an association between the level of AGE products in the vitreous and the clinical progression of DME (Stitt et al, 1998; Yokoi et al, 2005; Yu et al, 2008). To control appropriate responses, cells have a pattern recognition receptor (RAGE) to detect the levels of AGEs in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been reported in proliferative diabetic retinopathy and PVR [21,22]. Once retinal detachment occurs, the initial breakdown of the blood-retina barrier contributes part of the increased proteins of the vitreous in PVR [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increased expression of fI was detected in the vitreous of patients with proliferative diabetic retinopathy (PDR) [10], and the complement factors B, H, and I were detected in the PVR vitreous humor [35]. Whereas the authors conclude that their study provides proof of the destruction of blood retina barriers in the PVR samples because many common serum proteins, such as hemopexin, apolipoprotein A-I, A-II, H, and complement components significantly increased in PVR vitreous humor, our finding of a clear expression of fH and fH in epiretinal membranes identified RPE cells as an additional important source of complement regulatory proteins in these membranes.…”
Section: Discussionmentioning
confidence: 99%